Metal-Organic Framework Supporting Fe3O4 Prepared by Microwave in Couple With NTP to Eliminate VOCs From Biofuel - Gao, Yan; Cao, Qing; Guan, Ning; Zhang, Zhanchao; Fan, Guolan; Dou, Huawei; Li, Shijie; Wang, Qiang; Chen, Baoming (Frontiers in Energy Research, 2022)
In the production process of briquette biofuel, terpenes such as pinene and camphene, as well as non-terpenoid VOCs such as formic acid, acetaldehyde, and benzene, are generated during conditioning, drying and other procedures. Different catalysts of Fe3O4 supported by CoFe-ZIFs were prepared by thermal dissolution method and microwave dissolution method with changing the doping amount of iron. The structures of these catalysts were characterized by X-ray Diffraction (XRD), Fourier transform infrared spectrometer Fourier-Transformed InfraRed, thermogravimetric analysis (TG), and scanning electron microscope and the catalytic performance for α-pinene was tested on a fixed bed. The results show that, compared with the thermal dissolution method, the microwave dissolution method was easier to induce iron to form Fe3O4 grains with higher activity. At the same time, the grains did not affect the formation of CoFe-ZIFs structure. Fe3O4 supported on CoFe-ZIFs enhanced the catalytic activity and energy efficiency of the catalysts for α-pinene. Among the test samples, CoFe14-ZIF-W prepared by microwave method with Fe doping 14% mol exhibited the stable structural characteristics and the highest catalytic efficiency of 94.3% and energy efficiency of 8.11 g·kWh−1, which provided a further possibility of practical application for the removal of VOCs from biomass.